2015
DOI: 10.1039/c5ce00801h
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogels formed from Fmoc amino acids

Abstract: A number of Fmoc amino acids can be effective low molecular weight hydrogelators. The type of gel formed depends on the amino acid used and, in the case of FmocF, the final pH of the system. The single crystal structure of two of the gelators (FmocF and FmocY) have been determined and the data compared to the fibre X-ray diffraction data. FmocF, which forms metastable gels, crystallises easily and the data for the fibre phase and crystal phase are relatively similar. For FmocF, the fibre axis in b is consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
123
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(134 citation statements)
references
References 57 publications
(152 reference statements)
11
123
0
Order By: Relevance
“…This makes Fmoc-F-OH, Fmoc-Y-OH and Fmoc-W-OH self-assemble into hydrogels at a lower critical concentration than Fmoc-G-OH and Fmoc-I-OH without an aromatic group on the side chains (Table 1). 144 This phenomenon was also observed in the pentapeptide derivatives. The aromatic rings on N-termini of VYGGG and YGFGG together with the aromatic ring on Y and F side chains enabled the two pentapeptide derivatives to more easily assemble into a hydrogel compared to other pentapeptide derivatives (Table 1).…”
Section: π-π Stacking Interaction-based Hydrogelsmentioning
confidence: 65%
See 3 more Smart Citations
“…This makes Fmoc-F-OH, Fmoc-Y-OH and Fmoc-W-OH self-assemble into hydrogels at a lower critical concentration than Fmoc-G-OH and Fmoc-I-OH without an aromatic group on the side chains (Table 1). 144 This phenomenon was also observed in the pentapeptide derivatives. The aromatic rings on N-termini of VYGGG and YGFGG together with the aromatic ring on Y and F side chains enabled the two pentapeptide derivatives to more easily assemble into a hydrogel compared to other pentapeptide derivatives (Table 1).…”
Section: π-π Stacking Interaction-based Hydrogelsmentioning
confidence: 65%
“…140142 Recently, an aromatic moiety containing short peptides and N-terminal Fmoc-amino acids have been reported for robust self-assembly into supramolecular architectures for biomedical applications. 136138, 143, 144 Table 1 summarizes the categories of these gelators and their gelation conditions.…”
Section: π-π Stacking Interaction-based Hydrogelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, although it has been widely assumed that there is a link, there are a number of examples that now specifically show that packing is different in the gel phase and crystals grown even from the same solvent. [24][25][26] As a specific example, we showed that fiber X-ray diffraction data from the gel phase did not match the crystal structure of a crystal grown directly from the gel phase. 24 In many cases, the crystals formed in one solvent are compared with a gel formed in another.…”
Section: Introductionmentioning
confidence: 91%